Expresión de Citocinas Pro-Inflamatorias de Leucocitos de Alpaca (Vicugna pacos) Inducidos por el Extracto de Macroquistes de Sarcocystis aucheniae - Hinostroza S., Rocío (2015)
The aim of this research was to determine the expression of proinflammatory cytokines from alpaca leukocytes through the antigenic challenge with macrocyst extract of Sarcocystis aucheniae at various doses and exposure times. Leukocytes in a concentration of 500 000 cells/ml were exposed to concentrations of 0.5, 1, 50, 500 and 1000 ng of macrocyst extract ofS. aucheniae and incubated for 1, 12 and 24 h. The total messenger RNA (mRNA) was extracted for each treatment using Trizol and used to perform real-time RT-PCR with specific primers for cytokine TNF-α and interleukins IL-1α, IL-1β and IL-6. The generated mRNA levels of IL-1α and TNF-α at 1 h were detectable and higher in comparison to the calibrator (leukocytes not exposed to the extract). IL-1β increased at the 1 ng/ml concentration at 24 h showing a negative kinetic expression when compared with the untreated control group. IL-6 was not evidenced by RT-PCR real time. In addition, the leukocytes viability at 1, 12 and 24 h corroborated the toxic effect of the macrocyst extract ofS. aucheniae at high concentrations.